Nosema ceranae escapes fumagillin control in honey bees. - Wei-Fone Huang (Public Library of Science (PLoS), 2013)
Fumagillin is the only antibiotic approved for control of nosema disease in honey bees and has been extensively used in United States apiculture for more than 50 years for control of Nosema apis. It is toxic to mammals and must be applied seasonally and with caution to avoid residues in honey. Fumagillin degrades or is diluted in hives over the foraging season, exposing bees and the microsporidia to declining concentrations of the drug. We showed that spore production by Nosema ceranae, an emerging microsporidian pathogen in honey bees, increased in response to declining fumagillin concentrations, up to 100% higher than that of infected bees that have not been exposed to fumagillin. N. apis spore production was also higher, although not significantly so. Fumagillin inhibits the enzyme methionine aminopeptidase2 (MetAP2) in eukaryotic cells and interferes with protein modifications necessary for normal cell function. We sequenced the MetAP2 gene for apid Nosema species and determined that, although susceptibility to fumagillin differs among species, there are no apparent differences in fumagillin binding sites. Protein assays of uninfected bees showed that fumagillin altered structural and metabolic proteins in honey bee midgut tissues at concentrations that do not suppress microsporidia reproduction. The microsporidia, particularly N. ceranae, are apparently released from the suppressive effects of fumagillin at concentrations that continue to impact honey bee physiology. The current application protocol for fumagillin may exacerbate N. ceranae infection rather than suppress it.